Mucinous cystic tumor with CK20 and CDX2 expression of the thymus: Is this a benign counterpart of adenocarcinoma of the thymus, enteric type?. Issue 1 (18th November 2015) - Akiba, Jun; Harada, Hiroshi; Yokoyama, Shintaro; Hashiguchi, Toshihiro; Kawahara, Akihiko; Mitsuoka, Masahiro; Takamori, Shinzo; Yano, Hirohisa
Abstract : Primary thymic adenocarcinoma is extremely rare. Moreover, thymic pure epithelial benign neoplasms are extremely rare. We encountered a cystic tumor almost purely composed of goblet cell‐like mucus‐producing cells of the thymus. A mass lesion of the mediastinum was detected in a 54‐year‐old man. The gross specimen presented a unilocular cystic lesion containing abundant mucin, measuring 8 × 5.5 × 4.5 cm. Microscopic examination revealed a cystic tumor consisting of bland mucus‐producing cells resembling goblet cells and forming tiny daughter cysts within the dense fibrous capsule. No destructive growth or infiltration into surrounding thymic tissue was observed. Papillary growth was found in a small focus. Immunohistochemically, tumor cells were positive for cytokeratin 20 and caudal type homobox 2, which are representative markers of enteric differentiation. The patient has been well without any recurrence for approximately ten years after the operation. Thus, the tumor should be regarded as a mucinous cystic tumor in the thymus. Very recently, thymic adenocarcinoma with enteric differentiation was proposed as a novel subtype of thymic carcinoma. This case could be regarded as a benign counterpart of adenocarcinoma of the thymus, enteric type. A further follow‐up study is required to confirm the exact biological behavior of this tumor.